Wideband and high-selectivity dual-band filter for Ka-Band satellite antennas - Lima, E. B.; Costa, J. R.; Fernandes, C. A. (IEEE Antennas and Wireless Propagation Letters, 2017)
A dual-band miniaturized Ka-band filter is presented, taking advantage of transmission in cut-off rectangular waveguides periodically loaded in the E-plane with Split-Ring Resonators (SRRs). High selectivity, wide bandwidth and high out-of-band rejection are achieved in a compact form factor. The use of SRRs in a waveguide configuration proves to be a valid and promising solution for the design of dual-band filters. The filter is specifically designed for Ka-band and a prototype was manufactured and its performance measured, providing a reasonably flat transmission at both 20 and 30 GHz sub-bands. For both bands the power roll-off rate is higher than 55 dB/decade, translating into a sharper than 10 dB drop per 0.2 GHz in a 38 × 6.6 × 4.5 mm3 device. The filter half-power bandwidth is B_20 = 1.1 GHz at 20 GHz (18.4 - 19.5 GHz) and B_30 = 1.2 GHz at 30 GHz (27.8 - 29.0 GHz).